Leadership of Vocational High School Principals After the COVID-19 Pandemic In SMK Diponegoro Depok Yoyakarta - Maftuh; Choirul Muna (Journal of Indonesian Progressive Education, 2024)
Even though the COVID-19  pandemic has not ended, signs of improvement have been felt by many people. This is an opportunity and opportunity to improve due to problems that have hindered, including the education sector. There needs to be a further intervention related to the education sector, especially in the leadership aspect of the educational institution. This research aims to explore the leadership of school principals after the COVID-19  pandemic, especially in vocational high schools. With a descriptive qualitative approach through interviews, observation and literature view, at the Diponegoro Depok Vocational School, it was found that several roles had been carried out by the principal. As for the roles that can be seen from the aspect of supervision and managerial. In addition, in general, the principal can act as a facilitator, motivator, mentor, consultant, communicator, counselor, leader, innovator and is responsible for achieving educational goals. With the many roles that can be given by the principal, of course the hope is to advance education in Indonesia in general. With guarantees, they must be able to face increasingly complicated challenges, for example in developing an education system that is adaptive and able to adapt to the times.